Evaluation of the efficacy of two bioagents against the cotton Leafworm, Spodoptera Littoralis (Boisd.),using molecular characterization techniques - El-Sabagh, Marwa M.A. (2015)
Molecular studies have been carried out on 6th instar larvae of Spodoptera littoralis which treated in 2nd larval instars with LC50 of two bioagents named Viruset and Protecto at lx103 PIBs/ml and 3.2x102 IU/ml., respectively. Four random primers were used in this study to generate a fragmenting pattern as a tool to investigate the molecular differences between treated samples and control. The numbers of unique and common fragments generated by using these primers (OPOl, OPO2, OPO3 and OPO4) was recorded. It has been found that primer OP04 was the most powerful one in generating a unique informative fragmenting pattern; it gives 4 specific unique fragments. While the primer OPOl was the poorest one in generating an informative fragmenting pattern.
Includes references.
Summary in Arabic.
1
Keywords: Cotton leafworm -- Control; Insects -- Larvae; bioagents